Successful abdominal wound closure for treatment of severe peritonitis using negative pressure wound therapy with continuous mesh fascial traction: a case report - Hideki Kogo; Jun Hagiwara; Shiei Kin; Eiji Uchida (Surgical Case Reports)
Abstract Background Surgery for severe peritonitis often entails difficult wound closure and may require open abdominal management due to gut edema and/or concern of abdominal compartment syndrome. Negative pressure wound therapy (NPWT) is known to have good outcomes for wound closure after surgery for severe peritonitis. NPWT with continuous mesh fascial traction may result in even better outcomes, especially for fascial closure. Case presentation An 81-year-old man was hospitalized for abdominal pain. At admission, computed tomography (CT) demonstrated multiple liver metastases and a tumor perforating the sigmoid colon. Acute peritonitis due to perforated sigmoid colon cancer was diagnosed, and emergency peritonitis surgery and Hartmann’s operation were performed. However, at the end of the operation, the surgical abdominal wound could not be closed due to gut edema and concern of abdominal compartment syndrome. Thus, the abdominal wound was left open and NPWT was performed in the primary operation. In the second and subsequent operations, NPWT with mesh fascial traction was performed. The wound was ultimately closed in the fifth operation, which took place 9 days after the primary operation. Conclusions Treatment of severe peritonitis requires that gastroenterological surgeons learn some form of open abdominal management. This case suggests that NPWT with fascial mesh traction is a suitable solution. Furthermore, it does not require any special materials, and surgeons will find it easy to perform. In sum, NPWT with fascial mesh traction may be the preferred method of open abdominal management over other techniques currently available.